Correlation between Critical Thinking Ability and the Quality of Students' Independent Assignments in Histology Course - Nelda Anasthasia Serena; Masitah Masitah; Zenia Lutfi Kurniawati (SEARCH: Science Education Research Journal, 2025)
Critical thinking skills are a key component required in completing independent tasks (Sukenda, 2016). This study aims to analyze correlation between students' critical thinking skills and the quality of independent assignments in Histology courses. The research method used was a correlational quantitative approach involving 35 Biology Education study program students who were taking Histology courses. Data were collected through a histology context-based critical thinking test and independent assignment assessment using an analysis rubric. The correlation test results showed a positive correlation between critical thinking skills and the quality of students' independent assignments (r = 0.244, p < 0.05). This finding indicates that although there is a positive correlation coefficient between critical thinking ability and independent assignment quality, the significance value (Sig.) of 0.157 indicates that the correlation is not statistically significant. Based on this data, it can be concluded that there is no significant correlation between students' critical thinking skills and the quality of their independent assignments in the Histology course.